Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; émotions